The educational project of José Martí: a perspective from critical pedagogy - García Fallas, Jacqueline (2011)
This article presents an analysiscritical educational proposal writer, philosopherand nineteenth-century Cuban lawyer, José Martí. It takes a tour of the main concepts ofapproach to education as a political projectNational tico, it highlights the relationship betweeneducation and society, criticism of the traditional educational model and prospective view of the subject of education, and the role of implicit social transformationquote in Latin American education.